Governing through guidance: an analysis of educational guidance practices in an Italian lower secondary school. Issue 6 (2nd November 2019) - Romito, Marco
ABSTRACT: Current social policy discourse defines educational and career guidance as a key tool to enhance individual self-realisation while pursuing collective social objectives (economic growth, reduction of drop-out rate, social inclusion). Relying on Foucault's concept of governmentality, critical research has long destabilised this mainstream narrative by stressing that guidance polices constitute a technology of government through which the political ambition to govern is realised by shaping citizens' desires and ambitions. This article aims to provide an in-depth empirical analysis of how governing practices unfold within a concrete guidance setting. Based on ethnographic data, the essay focuses on guidance practices addressing 13–14-year-old students in Italy moving from comprehensive education to a tracked educational level. Particular emphasis is given to the role played by guidance forms, questionnaires and exercises. These materials, it is argued, enable particular technologies of the self that are key to involving individual in practices of self-government.